The Sunan (Divine Laws) of Nation Building - Malkawi, Fathi Hasan (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2023)
The concepts of Sunnah (pl. Sunan; in the broad sense of Divine Laws that govern human beings and nature), value, and nation are central in Qur’anic terminology. Though reflection on these concepts is always necessary, the present situation in the contemporary Muslim world makes it a top priority. This reflection becomes even more urgent when we realize the centrality in the life of nations of the culture of Sunan and of Sunani thinking, as well as the importance of contemplating on Sunan and extracting lessons as indicated in the Holy Qur’an. The founding and survival of a nation depend on several factors that support its existence, or, if lacking, cause its demise. This is Allah’s Sunnah, His Cosmic Divine Law. This study comprises four topics: a discussion of Sunnah as Divine Laws that govern human beings and nature; a discussion of the nation concept; an examination of the Divine Laws (Sunan) of nation-building by connecting the Divine Laws with the values and supporting factors, emphasizing the significance of higher values for a nation’s wellbeing; and lastly, it deals with the relationship between the Divine Law of Change and higher values, especially those that are essential for the wellbeing of nations.